Reactive and Non-Reactive Trace gas Exchange Within and Above an Amazonian Rainforest - Wolff, Stefan Aiko; Trebs, Ivonne; Manzi, Antonio Ocimar; Sá, Leonardo Deane de Abreu (Ciência e Natura, 2013)
In 2011 the currently highest atmospheric research tower of Amazonia was erected at the ATTO site (02°08’38,8’’S, 58°59’59,5’’W) (whereas ATTO stands for Amazon Tall Tower Observatory), which is monitoring concentration gradients regarding 5 trace gases (H2O, CO2, O3, NO, NO2) from 8 different heights between 0,05 m and 79,3 m, which enables the possibility to get new results regarding transport processes in and above the canopy. Never before there have been made profile measurements up to that height in the Amazonian rainforest.